Letters from Roger Casement to Herbert Ward about his travels through Nigeria - Casement, Roger, 1864-1916; Ward, Herbert, 1863-1919 (1904)
Casement describes his encounters with the locals and gives a sketch of one and his hairstyle.
Two letters on the same document, the first dated to 18th March and a manuscript in pencil, the other a dated to 30th March and manuscript in black ink.
Keywords: Casement, Roger, -- 1864-1916 -- Correspondence; Ward, Herbert, -- 1863-1919 -- Correspondence; Diplomatic and consular service, British; Colonies; Nigeria